CONSTRUCTION AND RESEARCH OF RADIAL CONTACT PRESSURE DISTRIBUTION MODEL FOR HEAVY-DUTY ENGINEERING WHEELS - YE Haozhe; WU Chaohua; QUAN Yongzhi; SHI Xiaoliang; LUO Wei (Jixie qiangdu)
Aiming at the inaccuracy of the finite element analysis (FEA) of heavy-duty engineering wheels under the radial loading condition, a new simulation analysis model based on the results of wheel-tire contact pressure test was established. Firstly, a stress data corresponding to the wheel under inflation pressure condition alone undergo testing, and a loading model for inflation pressure was formulated using a Gaussian function of 4th order. Secondly, a stress data collected while the wheel experiences combined inflation pressure and radial load were analyzed. The influence of inflation pressure was isolated, allowing for the development of a circumferential loading model and an axial loading model for the radial load, using a Fourier function of 4th order and a sinusoidal function of 4th order, respectively. Finally, the validation of the loading model was conducted through Ansys simulation. The outcomes demonstrate the calculation error of mere-approximately 1.943% in relation to the measured data for the key calibration points. Additionally, the observed stress distribution manifests a remarkable degree of consistency. This substantiates the accuracy and reliability inherent in the proposed radial contact pressure distribution model.